Functional Components of Cognitive Impairment in Multiple Sclerosis: A Cross-Sectional Investigation - Matias-Guiu, Jordi A.; Cortés-Martínez, Ana; Valles-Salgado, María; Oreja-Guevara, Celia; Pytel, Vanesa; Montero, Paloma; Moreno-Ramos, Teresa; Matias-Guiu, Jorge (Frontiers in Neurology, 2017)
Background: Cognitive impairment is frequent and disabling in multiple sclerosis (MS). Changes in information processing speed constitute the most important cognitive deficit in multiple sclerosis. However, given the clinical and topographical variability of the disease, cognitive impairment may vary greatly and appear in other forms in addition to slower information processing speed. Our aim was to determine the frequency of cognitive impairment, the principal cognitive domains and components involved in MS, and to identify factors associated with presence of cognitive impairment in these patients in a large series of patients. Methods: Cross-sectional study of 311 patients with MS (236 with relapsing-remitting MS [RRMS], 52 with secondary progressive MS [SPMS], and 23 with primary progressive MS [PPMS]). Patients’ cognitive function was assessed with a comprehensive neuropsychological assessment protocol. Patients displaying deficits in 2 or more cognitive domains were considered to have cognitive impairment associated with MS. We conducted a principal component analysis to detect different cognitive patterns by identifying clusters of tests highly correlated to one another. Results: Cognitive impairment was detected in 41.5% of the sample and it was more frequent in patients with SPMS and PPMS (P = 0.002). EDSS scores and education were independent predictors of cognitive impairment. Principal component analysis identified 7 clusters: attention and basic executive function (including information processing speed), planning and high-level executive function, verbal memory and language, executive and visuospatial performance time, fatigue-depression, visuospatial function, and basic attention and verbal/visual working memory. Mean scoring of components 2 (high-order executive functioning) and 3 (verbal memory-language) was higher in patients with RRMS than in those with PPMS (component 2) and SPMS (component 3). Conclusions: MS is linked to multiple cognitive profiles and disturbances in different domains. This suggests that cognitive alterations in MS are heterogeneous and affect other domains in addition to information processing speed.